Mitigating Brain Drain Through Employee Engagement: How Perceived Organizational Support, Employee Well-Being and Career Development Influence Zillennials’ Turnover Intention - Felisia Felisia; Titik Rosnani; Dody Pratama Marumpe; Ilzar Daud; Efa Irdhayanti (Komunitas Dosen Indonesia, 2025)
Brain drain has become popular among Zillennials reflecting their growing awareness of international career opportunities. This trend poses a challenge to Indonesia’s economic development particularly in sectors like banking where high employee turnover is common. As organizations face the threat of losing talented employees, adapting retention strategies is crucial to reduce turnover intention. Engaged employees are a key competitive advantage. This research aims to examine how perceived organizational support, employee well-being and career development influence turnover intention with employee engagement as a mediator. Data were collected from 258 Zillennial employees (born between 1992 and 2002) currently working at banks in Indonesia, each with at least six months of experience and awareness of international career trend like hashtag #KaburAjaDulu. Questionnaires were distributed via social media and data were analyzed using SmartPLS 4 with structural equation modelling (SEM). The findings demonstrate that perceived organizational support, employee well-being and career development positively influence employee engagement, while employee engagement negatively influences turnover intention. Notably, perceived organizational support and career development reduce turnover intention, while employee well-being’s effect on turnover intention is through mediation of employee engagement. Employee engagement plays a key mediating role of perceived organizational support, employee well-being, career development and turnover intention.